Combatting illicit trade on the EU border : a comparative perspective - Nowak, Celina (Springer, 2021)
This open access book provides the first-ever comparative study on criminal policy concerning the illicit trade of tobacco, conducted among four comparatively new EU Member States (Lithuania, Poland, Slovakia and Romania) and two "old" EU countries (Germany and Italy). The book addresses the national legal frameworks, current criminological situation regarding illicit trade of tobacco, and the practical challenges faced by national law enforcement authorities in the countries examined. It also considers the international framework, and concludes with a horizontal report. The objective of the book is to highlight legislative and practical challenges in the fight against illegal tobacco products at the national and transnational level, and to formulate recommendations for overcoming them more effectively in Europe.--